PENGARARUH BAURAN PEMASARAN TERHADAP PENJUALAN TIKET PADA PT. PELNI CABANG AMBON - Imran Tahalua (AkMen JURNAL ILMIAH, 2017)
The purpose of this research is to analyze the influence of marketing mix to KM-Tatamailau ticket sales at PT. PELNI Branch Ambon and to analyze the most dominant fakor effect on ticket sales KM-Tatamailau at PT. PELNI Ambon Branch. This research was conducted in Ambon city with population and samples of consumers who have purchased KM-Tatamailau tickets totaling 105 people (Slovin method). Data analysis used is descriptive to explain research data and description of research of Multiple Linear Regression. The results of research show that the results of research show that simultaneously the marketing mix consisting of product, price, promotion, and place have a significant effect on ticket sales KM-Tatamailau at PT. Pelni Branch of Ambon. Perve testing in a persial, marketing mix price berpangaruh most dominant against KM-Tatamilau ticket sales at PT. Pelni Branch of Ambon. There is a significant influence on the marketing mix consisting of Product, Price, Promotion, and Place on KM-Tatamailau ticket sales at PT. Pelni Branch of Ambon.